Root coverage with buccal fat pad placed on restored cervical abrasion: Case report with three-year follow-up - Harpreet Singh Grover; Sagrika Shukla; Ashi Chug; Kuldeep Singh (Wolters Kluwer Medknow Publications, 2018)
A patient was reported with Class II gingival recession (GR) of 5 mm. After restoring abrasion with glass ionomer cement, a full-thickness flap was raised and using blunt dissection through the buccinator and loose surrounding fascia buccal fat pad (BFP) was exposed into the mouth. It was easily spread over the maxillary roots of 14, 15, and 16. It was secured and immobilized using sutures. Postoperatively, the patient did not report swelling or trismus. At 3-year postoperative, gingival margin was at cementoenamel junction, stable and healthy and did not show any recession. Thus, it can be concluded that BFP for covering GR is an excellent technique. It is simple surgical procedure with easy handling of the flap. It provides excellent color and texture match and can also be considered as an excellent procedure for increasing the width of attached gingiva.